Effects of dynamic mold temperature control on melt pressure, cellular structure, and mechanical properties of microcellular injection-molded parts: An experimental study. Issue 5 (September 2019) - Dong, Guiwei; Zhao, Guoqun; Hou, Junji; Wang, Guilong; Mu, Yue
In this work, the effects of dynamic mold temperature control (DMTC) on melt pressure, cellular structure, and mechanical properties of microcellular injection molding (MIM)-molded parts are investigated experimentally. It is found that with the increase of the mold temperature, the duration of foaming pressure in the cooling stage increases. Meanwhile, the average cell diameter and cell diameter dispersion increases as well as the cell density decreases in MIM molded parts. The turning point of mold temperature after which the foaming pressure in the cooling stage and the cellular structure in MIM molded parts generate a significant change is around the glass transition temperature of the used plastic material. Under DMTC conditions, with the increase of mold temperature, the tensile strength, flexural strength, and impact strength of MIM molded specimens of single gate without weld line change a little, while the tensile strength, flexural strength of MIM molded specimens of double gates with weld line increase obviously. When the mold temperature increases to 120°C and over, the tensile strength, flexural strength of MIM molded specimens of double gates with weld line reach an equivalent level of specimens of single gate without weld line.